Effect of prohexadione-calcium onphotosynthetic and yield parameters in basmati rice (Oryza sativa L.) against lodging stress - Pal, Mamta; Johal, Norah; Thind, SK; Devi, Veena (ORYZA-An International Journal of Rice, 2023)
Basmati rice cultivators with longer internodes and shallow rooting system are prone to lodging especially during panicle development thus ultimately reducing yield, quality as well as efficiency of mechanical harvesting.Manipulation of GA status both via using exogenous application of GA or use of GA biosynthesis inhibitors or either by genetic alteration are regularly used to optimize plant growth and yields. Keeping this in mind the main objective of the study was to assess the role of Prohexadione-calcium (Pro-Ca) to reduce internode elongation against lodging stress without negatively affecting its productivity. A field experiment was conducted on three cultivars of basmati rice (Punjab Basmati 2, Punjab Basmati 3 and Pusa Basmati 1121) in split plot design at three concentration levels (foliar application) of Pro-Ca @5,10 and 20mg/l at vegetative and anthesis stage. Pro-Ca was found to uphill the concentrations of total chlorophyll (~9%)and Carotenoid(~4%) content in leaves at both vegetative and anthesis stages. An increment in the photosynthetic rate in flag leaf was also recorded in Pro-Ca treated sets in comparison to control, A significant increase in sucrose content in fully expanded leaf at vegetative and flag leaf at anthesis stage was recorded.Plant height significantly decreased in Pro-Ca treated plants and this decrease in height was recorded more with increased concentration of Pro-Ca. The increase in the yield contributing parameters viz., number of spikes/plant and grain/m2might be attributed to the blockage of gibberellins synthesis on account of Pro-Ca applicationin selected basmati rice variety PUSA 1121 by upregulating the photosynthetic rate (2%) andalso increase in sucrose content(2 to 18%).